Young People's Views on Accelerometer Use in Physical Activity Research: Findings from a User Involvement Investigation. (20th November 2012) - Kirby, Joanna; Tibbins, Carly; Callens, Claire; Lang, Beckie; Thorogood, Margaret; Tigbe, William; Robertson, Wendy
Abstract : The use of accelerometers to objectively measure physical activity is important in understanding young people's behaviours, as physical activity plays a key part in obesity prevention and treatment. A user-involvement qualitative study with young people aged 7–18 years (n = 35 ) was carried out to investigate views on accelerometer use to inform an obesity treatment research study. First impressions were often negative, with issues related to size and comfort reported. Unwanted attention from wearing an accelerometer and bullying risk were also noted. Other disadvantages included feeling embarrassed and not being able to wear the device for certain activities. Positive aspects included feeling "special" and having increased attention from friends. Views on the best time to wear accelerometers were mixed. Advice was offered on how to make accelerometers more appealing, including presenting them in a positive way, using a clip rather than elastic belt to attach, personalising the device, and having feedback on activity levels. Judgements over the way in which accelerometers are used should be made at the study development stage and based on the individual population. In particular, introducing accelerometers in a clear and positive way is important. Including a trial wearing period, considering practical issues, and providing incentives may help increase compliance.